Securing the Internet of Things - Safa Abood Nama; Kwther Abbood Neamah (Zien Journals, 2022)
There has been a surge in academic interest in the Internet of Things (IoT) in the last couple of years. There will be billions of "intelligent communications" "things" in the Internet of Things (IoT). The Internet of the future will be made up of a variety of devices that will connect to each other and extend the boundaries of the world. The Internet of Things (IoT) expands the functionality of devices that are already connected. Definition, architecture, key technologies and applications of the Internet of Things are all covered in depth in this study. There will be numerous definitions of IoT in the reports, to start with. After then, new means of implementing IoT will be explored. As a last step, several unsolved issues in IoT applications will be reviewed. Finally, the research community's most pressing challenges and possible solutions are discussed in this section.
Keywords: Internet of Things; Security Threats; Challenges